L'utilisation des preuves pour renforcer la formation pédagogique à travers les technologies à Madagascar - Koomar, Saalim; Moss Coflan, Caitlin; Rasolohéry, Hasiniavo (2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:analysis:nopdf; _r:AddedByZotZen; _zenodoETH

Sierra Leone Series: Plan International and the importance of community support for distance teacher professional development programmes - McBurnie, Chris; Saidu, Arthur; Rincon Casado, Eusebio; Shergill, Maggie (EdTech Hub, 2021)
Keywords: _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:analysis:nopdf; _r:AddedByZotZen

Sierra Leone series: Plan International and the importance of community support for distance teacher professional development programmes - Saidu, Arthur; Casado, Eusebio Rincon; Shergill, Maggie; McBurnie, Chris (EdTech Hub, 2021)
Over the past few months, the EdTech Hub team has analysed and mapped the EdTech research landscape in Sierra Leone. In doing so, we have met a number of individuals and organisations that are exploring if and how technology can support the country’s education sector.  In week four, we met with Arthur Saidu, Eusebio Rincon Casado and Maggie Shergill from…
Keywords: _DOILIVE; _EdTechHub_Output; ___working_potential_duplicate; _zenodoETH

Monitoring and evaluating radio in education - McBurnie, Chris (EdTech Hub, 2020)
Keywords: _EdTechHub_Output; dode_eth-src-eth; dode_eth-trf2-dode

Nine takeaways from our reviews of COVID-19 education responses - Chuang, Rachel; Kaye, Tom; Koomar, Saalim; McBurnie, Chris; Moss Coflan, Caitlin (EdTech Hub, 2020)
Regular readers will know about our Helpdesk, the on-demand support service we provide for FCDO advisers and World Bank staff to help them make evidence-informed decisions. Since the onset of coronavirus, the Helpdesk team has responded to requests from 15 countries across Africa, Asia, and the Middle…
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

Expert Consultation: Radio-Based Education in the Philippines - McBurnie, Chris (EdTech Hub, 2020)
These slides present an overview of educational radio programming with a particular focus on quality assurance and content design.
Keywords: C:Philippines; F: Helpdesk response; H:Radio; LP: English; _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; _cover:v2; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

The role of interactive radio instruction in the coronavirus (COVID-19) education response - McBurnie, Chris (EdTech Hub, 2020)
This is part of our coronavirus (COVID-19) and EdTech series. Every week that passes we see the number of classrooms closed due to COVID-19 increase. During these unprecedented times, the Hub’s mission — to increase the use of evidence-based decisions around EdTech — is more important than ever. We must make sure learning goes on. […]
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

The Role of Interactive Radio Instruction in the COVID-19 Education Response - McBurnie, Chris (Open Development & Education, 2020)
Reading Time: 3 minutes At a time when the COVID-19 pandemic has forced over 1.5 billion students out of school, governments in resource-constrained countries have looked to interactive radio instruction (IRI) to ensure educational continuity. In the past week, we spoke with the Rising Academy Network to consider what an IRI programme could look like and why policymakers have […]
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH; dode_eth-src-dode; dode_eth-trf2-dode